Liberty Laundry 1997 - Pickford, Joel:::::::::
The Liberty Laundry building, no longer owned by the Pickford family, 1997. The faded Liberty Laundry logos were painted by Rollin Pickford about 1930, when he was a student at Fresno State. He later transferred to Stanford University.